Pemanfaatan Influencer sebagai Strategi Komunikasi Pemasaran untuk Meningkatkan Brand Awareness Tinkerlust - Vidya Sri Gianthonove; Soraya Ratna Pratiwi (UNIVERSITAS KALBIS, 2022)
Influencer marketing is currently widely used by companies to conduct marketing activities. Influencers have many followers who believe in them as models or role models. Their ability to persuade makes them able to promote the product. The research method uses a qualitative approach. Data collection was done through online observations on Instagram influencers and Tinkerlust accounts, then interviews with Tinkerlust. This study uses a two step flow communication model. The two step flow model in this study aims to determine the pattern of influencer utilization as a marketing communication strategy through Instagram so as to increase Tinkerlust's brand awareness. The results revealed, influencers carried out marketing communication activities through: 1. Instagram stories, 2. photo uploads, 3. Instagram TV collaboration. The use of influencers through Instagram in increasing Tinkerlust's brand awareness has made Tinkerlust pass through the unaware brand stage and is currently in the position of brand recognition.